Ergonomics principles during learning and play for students at school and at home - Ewelina Grabska-Klein; Jacek Sołtys; Regina Wysocka; Malwina Mikuś-Nowak; Anna Brzęk (Śląski Uniwersytet Medyczny w Katowicach, 2024)
The aim of the study was to present the basic principles of ergonomics during a child's learning and play, taking into account the principles of physiotherapy regarding the positions adopted by the child. Biomechanical and kinesiological aspects of sitting posture and additional support points were described in detail. Correct and incorrect sitting positions were illustrated in the figures, with detailed descriptions provided in the text of the study, supported by legal regulations. The study can serve as a guide for children and parents on the discussed topic, but only for children and adolescents without existing postural abnormalities. In case of any postural defects or spinal deformities, it is advisable to consult a physiotherapist to approach each case individually.